Ethnomathematics: Cultural Exploration of Bangkalan Madura Regency in Mathematics Learning for Phase D: Etnomatematika: Eksplorasi Budaya Kabupaten Bangkalan Madura dalam Pembelajaran Matematika untuk Fase D - Muhakimah, Ihtiyatul; Arfinanti, Nurul (Jurnal Riset Pendidikan dan Inovasi Pembelajaran Matematika, 2024)
Culture is a way of life of a group of people that is passed down from generation to generation so it is unavoidable with everyday life. One way to change learners' poor perspective on mathematics is by linking it to local culture. An approach used to explain the relationship between culture and mathematics is called ethnomathematics. Bangkalan Regency deserves to be removed from the 2015-2019 list of disadvantaged regions. This is because Bangkalan Regency has a diverse culture. Some of them are batik and toron tana. The purpose of this research is to explore and examine the concept of mathematics in culture in Bangkalan Regency in Learning for phase D. This type of research is qualitative with an ethnographic approach. Data collection methods in the study consisted of observation, interviews, literature study, and documentation. The results of this study indicate that the culture in Bangkalan Regency has mathematical potential which includes ratios, number patterns, geometric transformations, similarity and congruence, curved-sided spaces, and opportunities. Some of these potentials are included in the learning outcomes for phase D of the elements of number, algebra, geometry, and data analysis and probability. These potentials can be implemented during apperception or motivation activities and can also be applied when developing math items.